Persinggungan Tindak Pidana Pencucian Uang dan Tindak Pidana Pemilu dalam Konteks Pendanaan Kampanye Pemilu - Sanjaya, Aditya Wiguna (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2023)
This paper aims to analyze the intersection between the PPTPPU Law and the Election Law in the context of election campaign funding, compare money laundering arrangements in the PPTPPU Law and the Election Law, and recommend ideal arrangements for handling money laundering in the context of future election campaign funding. The intersection between the PPTPPU Law and the Election Law regarding the provisions prohibiting receiving money from criminal acts has raised legal issues, namely which law should be applied, since both are special laws, furthermore this will also lead to different arrangements in each law. - the law, as well as PPATK not being involved in the handling of money laundering, which has been transformed into an election crime under the regime of the Election Law. The problem continues with the unregulated prohibition of giving election campaign fund contributions originating from criminal acts in the Election Law, and this shows the inconsistency of legislators in adopting the concept of money laundering into the Election Law. The method used is the normative legal research method. The results of the study show that based on the lex specialist systematic principle, the law that is applied is the Election Law. The Election Law does not stipulate active money laundering provisions, only regulates passive money laundering, while the PPTPPU Law regulates both; in the future, it is necessary to formulate active money laundering provisions in the Election Law.